Graduates’ English Communicative Skills and Professional Success: Perspectives from Universities and Industry stakeholders in Bangladesh - Karmaker, Protiva Rani; Al Hasan, Rakib (UNIB Press, 2025)
In today’s competitive employment market, graduates must be proficient in English communication to succeed professionally. Specifically, fluency in spoken English, professional writing skills, presentation skills, and interpersonal communication in English are critical factors that contribute to workplace success. This study investigates how far university graduates’ English communicative abilities contribute to their success in securing employment and performing effectively in the workplace. This paper broadly examines the needs of graduates for English communicative skills to progress in their careers. A mixed-method approach was employed, combining qualitative and quantitative data. The study was conducted at three purposively selected public universities in Bangladesh: the University of Dhaka, Jagannath University, and Jahangirnagar University. 50 students were purposively sampled, and 15 industry stakeholders from private banks, multinational companies, and English-medium schools in Dhaka were interviewed to explore workplace English proficiency expectations. The findings indicate a strong correlation between English communication skills and employment opportunities. However, many graduates face challenges in professional writing, public speaking, and business communication. Furthermore, the results highlight a considerable distance between the communication demands of the professional world and the English instruction provided at the university level, which results in unpreparedness for real-world communication challenges. In this regard, in enhance graduates' global competitiveness, the study recommends urgent curriculum modifications that prioritize business-oriented communication, industry-aligned training, and real-world English applications.